A multi-layer composite fiber core and preparation method thereof

By preparing a multi-layer composite fiber core, using mesoporous silica nanomicrospheres, composite highly absorbent resin, antibacterial additives and antibacterial treatment liquid, the problem of gel agglomeration and poor salt resistance of the existing absorbent core layer after liquid absorption is solved, achieving the improvement of high water absorption ratio and salt resistance, while enhancing the antibacterial and odor removal performance.

CN119345431BActive Publication Date: 2025-04-15GUANGDONG XINROU PAPER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411486266.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-04-15
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing absorbent core layer gel agglomerates after absorbing liquid, reducing the liquid absorption rate and multiple liquid absorption capabilities, and has poor salt resistance.

Method used

The preparation method of a multi-layer composite fiber core is adopted, including the preparation of mesoporous silica nanomicrospheres, composite hyperabsorbent resins, antibacterial additives and antibacterial treatment liquid. Through the combination and treatment of these materials, a multi-layer composite fiber core with high water absorption ratio and salt resistance is formed.

Benefits of technology

The water absorption ratio and salt resistance of the composite water-absorbing resin are significantly improved, and the antibacterial and deodorization properties of the multi-layer composite fiber core is enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a multi-layer composite fiber core and a preparation method thereof, belonging to the technical field of disposable sanitary products; the preparation process thereof comprises the following steps: preparing mesoporous silica nano-microspheres; preparing composite super absorbent resins; preparing antibacterial additives; preparing antibacterial and deodorizing viscose fibers; preparing antibacterial treatment liquids; preparing antibacterial treated fiber nets; and preparing multi-layer composite fiber cores. The present invention can significantly improve the water absorption rate of the prepared composite absorbent resin by mixing carboxymethyl corn straw cellulose with acrylic acid, acrylamide and mesoporous silica nano-microspheres, adding 2-acrylamide-2-methylpropane sulfonic acid, and reacting under the initiation of potassium persulfate, and can form multiple protection mechanisms to prevent salt ion interference, thereby effectively improving the salt resistance of the composite absorbent resin, and then improving its water absorption rate for artificial blood / urine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of disposable sanitary products, and in particular to a multi-layer composite fiber core and a preparation method thereof. Background Art

[0002] The composite fiber core is a core structural component composed of multiple materials (usually different types of fibers). It is widely used in sanitary products (such as diapers, sanitary napkins) and other fields. Taking diapers as an example, its materials can be divided into surface layer, guide layer, absorbent core layer and leak-proof bottom film from the inside to the outside. Among them, the absorbent core layer plays the most important liquid absorption and retention function of the diaper, and its absorption amount will directly affect the liquid absorption quality of the diaper.

[0003] The absorbent core layer should have the characteristics of fast and uniform liquid absorption, large liquid storage capacity, and flat structure after liquid absorption. It is usually composed of a composite of fiber materials and super absorbent resins. Most existing absorbent core layers use a mixture of SAP particles and fluff pulp. Although it has a large liquid absorption capacity and good side leakage prevention properties, the SAP particles therein tend to form larger gel aggregates after absorbing liquid, which reduces the liquid absorption rate and multiple liquid absorption capacity, and its salt resistance is poor. When there is salt in the environment, the water absorption efficiency of the SAP particles usually decreases.

[0004] Therefore, it is necessary to propose a multilayer composite fiber core with good salt resistance and high water absorption rate and a preparation method thereof. Summary of the invention

[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide a multi-layer composite fiber core and a preparation method thereof.

[0006] A method for preparing a multi-layer composite fiber core comprises the following steps:

[0007] S1: Preparation of mesoporous silica nanospheres

[0008] The anhydrous ethanol and concentrated ammonia water are uniformly mixed, and then hexadecyl trimethyl ammonium bromide is added, and after stirring and dispersing, sodium dodecyl sulfate and ethyl orthosilicate are added to react to prepare a precursor, and then the precursor is placed in isopropanol, after ultrasonic treatment, centrifuged, washed and dried to obtain mesoporous silica nanospheres;

[0009] S2: Preparation of composite superabsorbent resin

[0010] The corn stalks are ground and dispersed in deionized water, and then sodium hydroxide solution and sodium chloroacetate are added to react to prepare carboxymethyl corn stalk cellulose, and then acrylic acid, acrylamide, carboxymethyl corn stalk cellulose and the above-mentioned mesoporous silica nanospheres are fully mixed, and N,N′-methylenebisacrylamide, 2-acrylamide-2-methylpropanesulfonic acid and potassium persulfate are added to react to obtain a composite super absorbent resin;

[0011] S3: Preparation of antibacterial additives

[0012] Glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile) are fully stirred and mixed, and then added together with sodium p-styrene sulfonate into a mixed solution of anhydrous ethanol and deionized water, and the mixture is heated to react to prepare an intermediate, and then the intermediate and chitosan are dissolved to prepare an intermediate solution and a chitosan solution respectively, and finally the intermediate solution is added into the chitosan solution to react, and then hexadecyltrimethylammonium bromide is added to continue the reaction to obtain an antibacterial additive;

[0013] S4: Preparation of antibacterial and deodorizing viscose fibers

[0014] The antibacterial additive is dissolved in deionized water, and then activated clay powder is added, and after ultrasonic dispersion for 1-2 hours, it is added to the viscose spinning solution, stirred and mixed evenly, and allowed to stand for 2-3 hours. After filtering, degassing and aging, wet spinning is performed to obtain antibacterial and deodorizing viscose fibers;

[0015] S5: Preparation of antimicrobial treatment solution

[0016] β-cyclodextrin and thyme essential oil are respectively prepared into β-cyclodextrin dispersion and thyme essential oil solution, then the thyme essential oil solution is added into the β-cyclodextrin dispersion to prepare thyme essential oil microcapsules, which are then added into the aqueous solution of neem tree fruit extract, and after ultrasonic treatment, an antibacterial treatment solution is obtained;

[0017] S6: Preparation of antimicrobial treated web

[0018] The antibacterial and deodorizing viscose fiber and the hydrophilic polyolefin bicomponent fiber of equal weight are mixed and opened, and fed into a carding machine to form a fiber web, and then the fiber web is immersed in the antibacterial treatment liquid according to a solid-liquid ratio of 1g: (22-28)mL, and a cross-linking agent is added, and the fiber web is treated at 80-90°C for 1-2h, and then taken out and dried to obtain an antibacterial treated upper fiber web and an antibacterial treated lower fiber web;

[0019] S7: Preparation of multi-layer composite fiber core

[0020] The composite super absorbent resin is evenly added to the antibacterial treated upper fiber web and the antibacterial treated lower fiber web through an online powder spreading device, and then the antibacterial treated upper fiber web and the antibacterial treated lower fiber web loaded with the composite super absorbent resin are compounded and fed into a hot air blower for reinforcement to obtain a multi-layer composite fiber core.

[0021] Furthermore, S1 specifically includes the following steps:

[0022] S1.1: Mix anhydrous ethanol and concentrated ammonia water thoroughly at a volume ratio of (6-8):1, then add hexadecyltrimethylammonium bromide at a solid-liquid ratio of 1g:(145-155)mL, stir and disperse to obtain a mixed dispersion;

[0023] S1.2: Add sodium dodecyl sulfate and tetraethyl orthosilicate to the above mixed dispersion, and stir the mixture at a rate of 1000-1200 r / min for 3-4 hours, centrifuge, wash and dry to obtain a precursor;

[0024] S1.3: The above precursor is placed in isopropanol, stirred for 8-10 hours, and then ultrasonically treated for 30-40 minutes. After centrifugal separation, the precipitate is washed with isopropanol for 3-5 times, and then dried to obtain mesoporous silica nanospheres.

[0025] Furthermore, S2 specifically includes the following steps:

[0026] S2.1: Place corn stalks in a grinder, grind them thoroughly, pass through a 80-120 mesh sieve, and mix them thoroughly with deionized water at a solid-liquid ratio of 1 g: (90-100) mL to obtain a corn stalk suspension;

[0027] S2.2: Add a 20% sodium hydroxide solution by volume to the corn straw suspension, and heat and stir at 35-45°C for 1-2h, then raise the temperature to 70-80°C, add sodium chloroacetate at a solid-liquid ratio of 1g:(8-10)mL, and continue to react for 1-2h to obtain a carboxymethyl corn straw cellulose solution;

[0028] S2.3: filtering the carboxymethyl corn straw cellulose solution, washing with distilled water until neutral, and drying to obtain carboxymethyl corn straw cellulose;

[0029] S2.4: Add acrylic acid, acrylamide and carboxymethyl corn straw cellulose into deionized water, stir and mix thoroughly, then add the mesoporous silica nanoparticles prepared in step S1.3, and disperse them by ultrasonic for 10-20 minutes to obtain a mixed solution, wherein the mass ratio of acrylic acid, acrylamide, carboxymethyl corn straw cellulose and deionized water is (6-8): (1-2): 1: (25-35), and the solid-liquid ratio of mesoporous silica nanopowder to deionized water is 1g: (40-50)mL;

[0030] S2.5: Add N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid to the above mixed solution at a solid-liquid ratio of 1g:(3-5)g:(60-70)mL. After thorough mixing, add 10% by mass potassium persulfate solution, and heat under reflux at 60-70°C for 3-4h. After drying, crushing and sieving, a composite super absorbent resin is obtained, wherein the volume ratio of potassium persulfate solution to the mixed solution is 1:(35-45).

[0031] Furthermore, S3 specifically includes the following steps:

[0032] S3.1: Glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile) are thoroughly stirred and mixed in a mass ratio of (8-10):(12-13):1 to obtain a mixed monomer;

[0033] S3.2: Mix anhydrous ethanol and deionized water in a volume ratio of (5-6):1, heat to 70-80°C, add the above-mentioned mixed monomer and sodium p-styrene sulfonate, keep the temperature for 3-4h, dialyze and vacuum freeze-dry to obtain an intermediate;

[0034] S3.3: dissolving the intermediate in deionized water, and dissolving chitosan in acetic acid solution to obtain an intermediate solution and a chitosan solution;

[0035] S3.4: Add the intermediate solution to the chitosan solution, heat at 60-70°C for reaction for 6-8h, then add hexadecyltrimethylammonium bromide, continue the reaction for 3-4h, dialyze and vacuum freeze-dry to obtain an antibacterial additive.

[0036] Furthermore, S5 specifically includes the following steps:

[0037] S5.1: mixing β-cyclodextrin and thyme essential oil with deionized water and anhydrous ethanol, respectively, to obtain a β-cyclodextrin dispersion with a mass fraction of 60-70% and a thyme essential oil solution with a concentration of 75-85%;

[0038] S5.2: adding the thyme essential oil solution to an equal volume of the β-cyclodextrin dispersion, heating and shaking at 60-70°C for 2-3 hours, and then standing at 3-5°C for 8-10 hours to perform a curing reaction to obtain thyme essential oil microcapsules;

[0039] S5.3: Dissolve the neem fruit extract in distilled water at a solid-liquid ratio of 1 g:(10-12) mL, add the above-mentioned thyme essential oil microcapsules while stirring, and then ultrasonically treat for 20-30 minutes to obtain an antibacterial treatment solution, wherein the mass ratio of thyme essential oil microcapsules to neem fruit extract is 1:(3-4).

[0040] Furthermore, the mass ratio of sodium dodecyl sulfate to hexadecyltrimethylammonium bromide is 1:(11-13), and the volume ratio of tetraethyl orthosilicate to the mixed dispersion is 1:(110-120).

[0041] Furthermore, the solid-liquid ratio of sodium p-styrene sulfonate to the total amount of anhydrous ethanol and deionized water is 1 g:(7-9) mL, and the mass ratio of sodium p-styrene sulfonate to the mixed monomer is (1.1-1.2):1.

[0042] Furthermore, the solid-liquid ratio of the antibacterial additive to deionized water is 1 g: (20-30) mL, and the mass ratio of activated clay powder to the antibacterial additive is 1: (13-15), and the addition amount of activated clay powder is (0.01-0.03) g / mL viscose spinning solution.

[0043] Furthermore, the antibacterial treated upper fiber web uses antibacterial and deodorizing viscose fiber with a linear density of 1.67 dtex and hydrophilic polyolefin bicomponent fiber with a linear density of 6.67 dtex, and the antibacterial treated lower fiber web uses antibacterial and deodorizing viscose fiber with a linear density of 1.67 dtex and hydrophilic polyolefin bicomponent fiber with a linear density of 2.22 dtex.

[0044] A multi-layer composite fiber core is prepared by any of the above-mentioned methods for preparing a multi-layer composite fiber core.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The present invention grinds and sieves corn stalks to prepare a corn stalk suspension, then adds sodium hydroxide solution and sodium chloroacetate to react respectively to prepare carboxymethyl corn stalk cellulose, then mixes the carboxymethyl corn stalk cellulose with acrylic acid, acrylamide and mesoporous silica nanospheres, and adds N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid to react under the initiation of potassium persulfate. On the one hand, due to the combined action of carboxymethyl corn stalk fiber, N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and acrylamide can be reacted. The composite super absorbent resin made of amide composite forms a denser and larger three-dimensional network structure, and the addition of mesoporous silica nanopowder can improve the network structure stability of the composite super absorbent resin, thereby significantly improving the water absorption rate of the prepared composite absorbent resin. On the other hand, due to the high salt resistance of acrylamide, the steric hindrance of carboxymethyl corn straw cellulose and the negatively charged groups of 2-acrylamide-2-methylpropane sulfonic acid work together to form multiple protection mechanisms to prevent salt ion interference, thereby effectively improving the salt resistance of the composite absorbent resin, and then improving its water absorption rate for artificial blood / urine.

[0047] 2. The present invention first mixes monomers of glycidyl methacrylate, butyl acrylate and 2,2″-azo (2-methylpropionitrile), then adds the mixed monomers and sodium p-styrene sulfonate into a mixed solution of anhydrous ethanol and deionized water for reaction to prepare an intermediate, then dissolves the intermediate in deionized water, adds chitosan solution and hexadecyltrimethylammonium bromide for reaction to prepare an antibacterial additive, and adds the antibacterial additive together with activated clay powder into a viscose spinning solution and spins into an antibacterial and deodorizing viscose fiber. On the one hand, due to the epoxy groups in the molecular chain of the intermediate Combined with the amino group in the chitosan structure, the water solubility of the antibacterial additive is enhanced, which is conducive to better interaction with bacteria. On the other hand, due to the ion exchange between the sodium sulfonate group in the intermediate molecular chain and hexadecyltrimethylammonium bromide, the positive charge density on the surface of the antibacterial additive is increased to improve its antibacterial activity. The activated white clay powder contains a large number of micropores and has good adsorption properties, which can effectively absorb odorous gases. Therefore, after the antibacterial and deodorizing viscose fiber is made into a multi-layer composite fiber core, the antibacterial and deodorizing properties of the multi-layer composite fiber core can be improved.

[0048] 3. The present invention prepares thyme essential oil microcapsules using thyme essential oil and β-cyclodextrin as raw materials, and then mixes the thyme essential oil microcapsules with neem tree fruit extract to prepare an antibacterial treatment liquid. After the fiber web made of antibacterial and deodorizing viscose fiber and hydrophilic polyolefin two-component fiber is treated with the antibacterial treatment liquid, the thyme essential oil microcapsules can synergistically improve the antibacterial properties of the fiber web with the neem tree fruit extract, thereby further improving the antibacterial properties of the multi-layer composite fiber core made of the fiber web. DETAILED DESCRIPTION

[0049] The following is a detailed description of a multi-layer composite fiber core and a preparation method thereof provided by the present invention in conjunction with specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies.

[0050] Example 1

[0051] A method for preparing a multi-layer composite fiber core comprises the following steps:

[0052] S1: Preparation of mesoporous silica nanospheres

[0053] S1.1: Thoroughly mix anhydrous ethanol and concentrated ammonia water at a volume ratio of 6:1, then add hexadecyltrimethylammonium bromide at a solid-liquid ratio of 1g:145mL, stir and disperse to obtain a mixed dispersion;

[0054] S1.2: adding sodium dodecyl sulfate and tetraethyl orthosilicate to the above-mentioned mixed dispersion, and stirring the mixture at a rate of 1000 r / min for 3 h, centrifuging, washing and drying to obtain a precursor, wherein the mass ratio of sodium dodecyl sulfate to hexadecyltrimethylammonium bromide is 1:11, and the volume ratio of tetraethyl orthosilicate to the mixed dispersion is 1:110;

[0055] S1.3: placing the above precursor in isopropanol, stirring for 8 hours, and then ultrasonically treating for 30 minutes. After centrifugal separation, washing the precipitate with isopropanol for 3 times, and then drying, to obtain mesoporous silica nanospheres;

[0056] S2: Preparation of composite superabsorbent resin

[0057] S2.1: Place corn stalks in a grinder, grind them thoroughly, pass through an 80-mesh sieve, and mix them thoroughly with deionized water at a solid-liquid ratio of 1g:90mL to obtain a corn stalk suspension;

[0058] S2.2: Add 20% sodium hydroxide solution by volume ratio of 1:7 to the corn straw suspension, heat and stir at 35°C for 1 hour, then heat to 70°C, add sodium chloroacetate by solid-liquid ratio of 1g:8mL, and continue to react for 1 hour to obtain carboxymethyl corn straw cellulose solution;

[0059] S2.3: filtering the carboxymethyl corn straw cellulose solution, washing with distilled water until neutral, and drying to obtain carboxymethyl corn straw cellulose;

[0060] S2.4: Add acrylic acid, acrylamide and carboxymethyl corn straw cellulose into deionized water, stir and mix thoroughly, then add the mesoporous silica nanoparticles prepared in step S1.3, and ultrasonically disperse for 10 minutes to obtain a mixed solution, wherein the mass ratio of acrylic acid, acrylamide, carboxymethyl corn straw cellulose and deionized water is 6:1:1:25, and the solid-liquid ratio of mesoporous silica nanopowder to deionized water is 1g:40mL;

[0061] S2.5: Add N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid to the above mixed solution at a solid-liquid ratio of 1g:3g:60mL, mix thoroughly, then add 10% by mass potassium persulfate solution, heat and reflux at 60°C for 3h, dry, crush and sieve to obtain a composite super absorbent resin, wherein the volume ratio of potassium persulfate solution to the mixed solution is 1:35;

[0062] S3: Preparation of antibacterial additives

[0063] S3.1: Glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile) were fully stirred and mixed in a mass ratio of 8:12:1 to obtain a mixed monomer;

[0064] S3.2: Anhydrous ethanol and deionized water are stirred and mixed in a volume ratio of 5:1, and after heating to 70°C, the above-mentioned mixed monomer and sodium p-styrene sulfonate are added, and the reaction is kept warm for 3 hours, and dialyzed and vacuum freeze-dried to obtain an intermediate, wherein the solid-liquid ratio of sodium p-styrene sulfonate to the total amount of anhydrous ethanol and deionized water is 1 g:7 mL, and the mass ratio of sodium p-styrene sulfonate to the mixed monomer is 1.1:1;

[0065] S3.3: dissolving the intermediate in deionized water, and dissolving chitosan in acetic acid solution to obtain an intermediate solution and a chitosan solution;

[0066] S3.4: adding the intermediate solution to the chitosan solution, heating at 60°C for 6 hours, then adding hexadecyltrimethylammonium bromide, continuing the reaction for 3 hours, dialyzing and vacuum freeze-drying to obtain an antibacterial additive;

[0067] S4: Preparation of antibacterial and deodorizing viscose fibers

[0068] The antibacterial additive is dissolved in deionized water, and then activated clay powder is added. After ultrasonic dispersion for 1 hour, the mixture is added to the viscose spinning solution, stirred and mixed evenly, and allowed to stand for 2 hours. After filtering, degassing and aging, wet spinning is performed to obtain antibacterial and deodorizing viscose fibers, wherein the solid-liquid ratio of the antibacterial additive to deionized water is 1 g: 20 mL, and the mass ratio of the activated clay powder to the antibacterial additive is 1: 13, and the amount of activated clay powder added is 0.01 g / mL of viscose spinning solution;

[0069] S5: Preparation of antimicrobial treatment solution

[0070] S5.1: mixing β-cyclodextrin and thyme essential oil with deionized water and anhydrous ethanol, respectively, to obtain a β-cyclodextrin dispersion with a mass fraction of 60% and a thyme essential oil solution with a concentration of 75%;

[0071] S5.2: adding the thyme essential oil solution to an equal volume of the β-cyclodextrin dispersion, heating and shaking at 60° C. for 2 h, and then standing at 3° C. for 8 h to perform a curing reaction to obtain thyme essential oil microcapsules;

[0072] S5.3: dissolving the neem fruit extract in distilled water at a solid-liquid ratio of 1 g:10 mL, adding the thyme essential oil microcapsules while stirring, and then ultrasonically treating for 20 minutes to obtain an antibacterial treatment solution, wherein the mass ratio of the thyme essential oil microcapsules to the neem fruit extract is 1:3;

[0073] S6: Preparation of antimicrobial treated web

[0074] The antibacterial and deodorizing viscose fiber and the hydrophilic polyolefin bicomponent fiber of equal mass are mixed and opened, and fed into a carding machine to form a fiber web, and then the fiber web is immersed in the antibacterial treatment liquid according to a solid-liquid ratio of 1g:22mL, and a cross-linking agent is added, and the fiber web is treated at 80°C for 1h, taken out and dried to obtain an antibacterial treated upper fiber web and an antibacterial treated lower fiber web, wherein the antibacterial treated upper fiber web adopts the antibacterial and deodorizing viscose fiber with a linear density of 1.67dtex and the hydrophilic polyolefin bicomponent fiber with a linear density of 6.67dtex, and the antibacterial treated lower fiber web adopts the antibacterial and deodorizing viscose fiber with a linear density of 1.67dtex and the hydrophilic polyolefin bicomponent fiber with a linear density of 2.22dtex;

[0075] S7: Preparation of multi-layer composite fiber core

[0076] The composite super absorbent resin is evenly added to the antibacterial treated upper fiber web and the antibacterial treated lower fiber web through an online powder spreading device, and then the antibacterial treated upper fiber web and the antibacterial treated lower fiber web loaded with the composite super absorbent resin are compounded and fed into a hot air blower for reinforcement to obtain a multi-layer composite fiber core.

[0077] Example 2

[0078] A method for preparing a multi-layer composite fiber core comprises the following steps:

[0079] S1: Preparation of mesoporous silica nanospheres

[0080] S1.1: Thoroughly mix anhydrous ethanol and concentrated ammonia water at a volume ratio of 7:1, then add hexadecyltrimethylammonium bromide at a solid-liquid ratio of 1g:150mL, stir and disperse to obtain a mixed dispersion;

[0081] S1.2: adding sodium dodecyl sulfate and tetraethyl orthosilicate to the above-mentioned mixed dispersion, and stirring the mixture at a rate of 1100 r / min for 3.5 h, centrifuging, washing and drying to obtain a precursor, wherein the mass ratio of sodium dodecyl sulfate to hexadecyltrimethylammonium bromide is 1:12, and the volume ratio of tetraethyl orthosilicate to the mixed dispersion is 1:115;

[0082] S1.3: placing the above precursor in isopropanol, stirring for 9 hours, and then ultrasonically treating for 35 minutes. After centrifugal separation, washing the precipitate with isopropanol for 4 times, and then drying, to obtain mesoporous silica nanospheres;

[0083] S2: Preparation of composite superabsorbent resin

[0084] S2.1: Place corn stalks in a grinder, grind them thoroughly, pass through a 100-mesh sieve, and mix them thoroughly with deionized water at a solid-liquid ratio of 1g:95mL to obtain a corn stalk suspension;

[0085] S2.2: Add a 20% sodium hydroxide solution by volume ratio of 1:7.5 to the corn straw suspension, heat and stir at 40°C for 1.5h, then heat to 75°C, add sodium chloroacetate by solid-liquid ratio of 1g:9mL, and continue to react for 1.5h to obtain a carboxymethyl corn straw cellulose solution;

[0086] S2.3: filtering the carboxymethyl corn straw cellulose solution, washing with distilled water until neutral, and drying to obtain carboxymethyl corn straw cellulose;

[0087] S2.4: Add acrylic acid, acrylamide and carboxymethyl corn straw cellulose to deionized water, stir and mix thoroughly, then add the mesoporous silica nanoparticles prepared in step S1.3, and ultrasonically disperse for 15 minutes to obtain a mixed solution, wherein the mass ratio of acrylic acid, acrylamide, carboxymethyl corn straw cellulose and deionized water is 7:1.5:1:30, and the solid-liquid ratio of mesoporous silica nanopowder to deionized water is 1g:45mL;

[0088] S2.5: Add N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid to the above mixed solution at a solid-liquid ratio of 1g:4g:65mL, mix thoroughly, then add 10% by mass potassium persulfate solution, heat and reflux at 65°C for 3.5h, dry, crush and sieve to obtain a composite super absorbent resin, wherein the volume ratio of potassium persulfate solution to the mixed solution is 1:40;

[0089] S3: Preparation of antibacterial additives

[0090] S3.1: Glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile) were fully stirred and mixed in a mass ratio of 9:12.5:1 to obtain a mixed monomer;

[0091] S3.2: Anhydrous ethanol and deionized water are stirred and mixed in a volume ratio of 5.5:1, and after heating to 75°C, the above-mentioned mixed monomer and sodium p-styrene sulfonate are added, and the reaction is kept warm for 3.5 hours. The intermediate is obtained by dialyzing and vacuum freeze-drying, wherein the solid-liquid ratio of sodium p-styrene sulfonate to the total amount of anhydrous ethanol and deionized water is 1 g:8 mL, and the mass ratio of sodium p-styrene sulfonate to the mixed monomer is 1.15:1;

[0092] S3.3: dissolving the intermediate in deionized water, and dissolving chitosan in acetic acid solution to obtain an intermediate solution and a chitosan solution;

[0093] S3.4: adding the intermediate solution to the chitosan solution, heating at 65°C for 7 hours, then adding hexadecyltrimethylammonium bromide, continuing the reaction for 3.5 hours, dialyzing and vacuum freeze-drying to obtain an antibacterial additive;

[0094] S4: Preparation of antibacterial and deodorizing viscose fibers

[0095] The antibacterial additive was dissolved in deionized water, and then activated clay powder was added. After ultrasonic dispersion for 1.5 hours, the mixture was added to the viscose spinning solution, stirred and mixed evenly, and allowed to stand for 2.5 hours. After filtering, degassing and aging, wet spinning was performed to obtain antibacterial and deodorizing viscose fibers, wherein the solid-liquid ratio of the antibacterial additive to deionized water was 1 g: 25 mL, and the mass ratio of the activated clay powder to the antibacterial additive was 1: 14, and the amount of activated clay powder added was 0.02 g / mL of viscose spinning solution;

[0096] S5: Preparation of antimicrobial treatment solution

[0097] S5.1: mixing β-cyclodextrin and thyme essential oil with deionized water and anhydrous ethanol, respectively, to obtain a β-cyclodextrin dispersion with a mass fraction of 65% and a thyme essential oil solution with a concentration of 80%;

[0098] S5.2: adding the thyme essential oil solution to an equal volume of the β-cyclodextrin dispersion, heating and shaking at 65° C. for 2.5 h, and then standing at 4° C. for 9 h to perform a curing reaction to obtain thyme essential oil microcapsules;

[0099] S5.3: dissolving the neem fruit extract in distilled water at a solid-liquid ratio of 1 g:11 mL, adding the thyme essential oil microcapsules while stirring, and then ultrasonically treating for 25 minutes to obtain an antibacterial treatment solution, wherein the mass ratio of the thyme essential oil microcapsules to the neem fruit extract is 1:3.5;

[0100] S6: Preparation of antimicrobial treated web

[0101] The antibacterial and deodorizing viscose fiber and the hydrophilic polyolefin bicomponent fiber of equal mass are mixed and opened, and fed into a carding machine to form a fiber web, and then the fiber web is immersed in the antibacterial treatment liquid according to a solid-liquid ratio of 1g:25mL, and a cross-linking agent is added, and the fiber web is treated at 85°C for 1.5h, taken out and dried to obtain an antibacterial treated upper fiber web and an antibacterial treated lower fiber web, wherein the antibacterial treated upper fiber web adopts the antibacterial and deodorizing viscose fiber with a linear density of 1.67dtex and the hydrophilic polyolefin bicomponent fiber with a linear density of 6.67dtex, and the antibacterial treated lower fiber web adopts the antibacterial and deodorizing viscose fiber with a linear density of 1.67dtex and the hydrophilic polyolefin bicomponent fiber with a linear density of 2.22dtex;

[0102] S7: Preparation of multi-layer composite fiber core

[0103] The composite super absorbent resin is evenly added to the antibacterial treated upper fiber web and the antibacterial treated lower fiber web through an online powder spreading device, and then the antibacterial treated upper fiber web and the antibacterial treated lower fiber web loaded with the composite super absorbent resin are compounded and fed into a hot air blower for reinforcement to obtain a multi-layer composite fiber core.

[0104] Example 3

[0105] A method for preparing a multi-layer composite fiber core comprises the following steps:

[0106] S1: Preparation of mesoporous silica nanospheres

[0107] S1.1: Thoroughly mix anhydrous ethanol and concentrated ammonia water at a volume ratio of 8:1, then add hexadecyltrimethylammonium bromide at a solid-liquid ratio of 1g:155mL, stir and disperse to obtain a mixed dispersion;

[0108] S1.2: adding sodium dodecyl sulfate and tetraethyl orthosilicate to the above-mentioned mixed dispersion, and stirring the mixture at a rate of 1200 r / min for 4 hours, centrifuging, washing and drying to obtain a precursor, wherein the mass ratio of sodium dodecyl sulfate to hexadecyltrimethylammonium bromide is 1:13, and the volume ratio of tetraethyl orthosilicate to the mixed dispersion is 1:120;

[0109] S1.3: placing the above precursor in isopropanol, stirring for 10 hours, and then ultrasonically treating for 40 minutes. After centrifugal separation, washing the precipitate with isopropanol for 5 times, and then drying, to obtain mesoporous silica nanospheres;

[0110] S2: Preparation of composite superabsorbent resin

[0111] S2.1: Place corn stalks in a grinder, grind them thoroughly, pass through a 120-mesh sieve, and mix them thoroughly with deionized water at a solid-liquid ratio of 1 g:100 mL to obtain a corn stalk suspension;

[0112] S2.2: Add a 20% sodium hydroxide solution by volume ratio of 1:8 to the corn straw suspension, heat and stir at 45°C for 2 h, then heat to 80°C, add sodium chloroacetate by solid-liquid ratio of 1 g:10 mL, and continue to react for 2 h to obtain a carboxymethyl corn straw cellulose solution;

[0113] S2.3: filtering the carboxymethyl corn straw cellulose solution, washing with distilled water until neutral, and drying to obtain carboxymethyl corn straw cellulose;

[0114] S2.4: Add acrylic acid, acrylamide and carboxymethyl corn straw cellulose into deionized water, stir and mix thoroughly, then add the mesoporous silica nanoparticles prepared in step S1.3, and ultrasonically disperse for 20 minutes to obtain a mixed solution, wherein the mass ratio of acrylic acid, acrylamide, carboxymethyl corn straw cellulose and deionized water is 8:2:1:35, and the solid-liquid ratio of mesoporous silica nanopowder to deionized water is 1g:50mL;

[0115] S2.5: Add N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid to the above mixed solution at a solid-liquid ratio of 1g:5g:70mL, mix thoroughly, then add 10% by mass potassium persulfate solution, heat and reflux at 70°C for 4h, dry, crush and sieve to obtain a composite super absorbent resin, wherein the volume ratio of potassium persulfate solution to the mixed solution is 1:45;

[0116] S3: Preparation of antibacterial additives

[0117] S3.1: Glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile) were fully stirred and mixed in a mass ratio of 10:13:1 to obtain a mixed monomer;

[0118] S3.2: Anhydrous ethanol and deionized water are stirred and mixed in a volume ratio of 6:1, and after heating to 80°C, the above-mentioned mixed monomer and sodium p-styrene sulfonate are added, and the reaction is kept warm for 4 hours, and dialyzed and vacuum freeze-dried to obtain an intermediate, wherein the solid-liquid ratio of sodium p-styrene sulfonate to the total amount of anhydrous ethanol and deionized water is 1 g:9 mL, and the mass ratio of sodium p-styrene sulfonate to the mixed monomer is 1.2:1;

[0119] S3.3: dissolving the intermediate in deionized water, and dissolving chitosan in acetic acid solution to obtain an intermediate solution and a chitosan solution;

[0120] S3.4: adding the intermediate solution to the chitosan solution, heating at 70°C for 8 hours, then adding hexadecyltrimethylammonium bromide, continuing the reaction for 4 hours, dialyzing and vacuum freeze-drying to obtain an antibacterial additive;

[0121] S4: Preparation of antibacterial and deodorizing viscose fibers

[0122] The antibacterial additive is dissolved in deionized water, and then activated clay powder is added. After ultrasonic dispersion for 2 hours, it is added to the viscose spinning solution, stirred and mixed evenly, and allowed to stand for 3 hours. After filtering, degassing and aging, wet spinning is performed to obtain antibacterial and deodorizing viscose fibers, wherein the solid-liquid ratio of the antibacterial additive to deionized water is 1 g:30 mL, and the mass ratio of the activated clay powder to the antibacterial additive is 1:15, and the addition amount of the activated clay powder is 0.03 g / mL of viscose spinning solution;

[0123] S5: Preparation of antimicrobial treatment solution

[0124] S5.1: mixing β-cyclodextrin and thyme essential oil with deionized water and anhydrous ethanol respectively to obtain a β-cyclodextrin dispersion with a mass fraction of 70% and a thyme essential oil solution with a concentration of 85%;

[0125] S5.2: adding the thyme essential oil solution to an equal volume of the β-cyclodextrin dispersion, heating and shaking at 70° C. for 3 h, and then standing at 5° C. for 10 h to perform a curing reaction to obtain thyme essential oil microcapsules;

[0126] S5.3: dissolving the neem fruit extract in distilled water at a solid-liquid ratio of 1 g:12 mL, adding the thyme essential oil microcapsules while stirring, and then ultrasonically treating for 30 minutes to obtain an antibacterial treatment solution, wherein the mass ratio of the thyme essential oil microcapsules to the neem fruit extract is 1:4;

[0127] S6: Preparation of antimicrobial treated web

[0128] The antibacterial and deodorizing viscose fiber and the hydrophilic polyolefin bicomponent fiber of equal mass are mixed and opened, and fed into a carding machine to form a fiber web, and then the fiber web is immersed in the antibacterial treatment liquid according to a solid-liquid ratio of 1g:28mL, and a cross-linking agent is added, and the fiber web is treated at 90°C for 2h, taken out and dried to obtain an antibacterial treated upper fiber web and an antibacterial treated lower fiber web, wherein the antibacterial treated upper fiber web adopts the antibacterial and deodorizing viscose fiber with a linear density of 1.67dtex and the hydrophilic polyolefin bicomponent fiber with a linear density of 6.67dtex, and the antibacterial treated lower fiber web adopts the antibacterial and deodorizing viscose fiber with a linear density of 1.67dtex and the hydrophilic polyolefin bicomponent fiber with a linear density of 2.22dtex;

[0129] S7: Preparation of multi-layer composite fiber core

[0130] The composite super absorbent resin is evenly added to the antibacterial treated upper fiber web and the antibacterial treated lower fiber web through an online powder spreading device, and then the antibacterial treated upper fiber web and the antibacterial treated lower fiber web loaded with the composite super absorbent resin are compounded and fed into a hot air blower for reinforcement to obtain a multi-layer composite fiber core.

[0131] Comparative Example 1

[0132] The difference between this comparative example 1 and example 1 is that step S1 and step S1 are removed, and the composite super absorbent resin in step S7 is replaced by an equal amount of SAP particles.

[0133] Comparative Example 2

[0134] The difference between Comparative Example 3 and Example 1 is that the mesoporous silica nanospheres in step S2 are removed.

[0135] Comparative Example 3

[0136] The difference between Comparative Example 3 and Example 1 is that step S3 is removed, and the antibacterial additive and activated clay powder in step S4 are removed.

[0137] Comparative Example 4

[0138] The difference between Comparative Example 4 and Example 1 is that step S5 is removed, and the antibacterial treatment liquid in step S6 is removed.

[0139] Comparative Example 5

[0140] The difference between Comparative Example 5 and Example 1 is that the thyme essential oil microcapsules in step S5 are replaced with an equal amount of neem tree fruit extract.

[0141] Comparative Example 6

[0142] The difference between Comparative Example 6 and Example 1 is that the neem fruit extract in step S5 is replaced by an equal amount of thyme essential oil microcapsules.

[0143] Performance Testing

[0144] Test 1:

[0145] The water absorption rate of the multi-layer composite fiber core prepared in Examples 1-3 and Comparative Examples 1-2 was tested with reference to GB / T 24218.6-2010 "Test methods for textile nonwovens Part 6: Determination of absorbency". The sample size was 100 mm × 100 mm. The dry sample mass m1 was weighed. Then, the sample was completely immersed in pure water. After 1 minute, it was immediately taken out and hung vertically for 2 minutes. The sample mass m2 was weighed. Liquid absorption rate L c It is expressed as the ratio of the mass of liquid absorbed by the sample to the dry mass of the sample, as shown in the following formula:

[0146] L c =(m2-m1) / m1;

[0147] The pure water in Test 1 was replaced with 0.9% NaCl solution and artificial blood, and the absorption rate of saline and the absorption rate of water by artificial blood were tested. The results are shown in Table 1.

[0148] Table 1: Comparative table of water absorption, saline and artificial blood absorption rate performance test of Examples 1-3 and Comparative Examples 1-2

[0149] Water absorption rate Salt water absorption rate Artificial blood water absorption rate Example 1 232.4 89.8 77.5 Example 2 232.7 89.7 77.4 Example 3 231.9 90.1 77.7 Comparative Example 1 217.3 47.3 32.5 Comparative Example 2 224.2 82.2 69.8

[0150] It can be seen from Table 1 that the water absorption rate, salt water absorption rate and artificial blood absorption rate of the multi-layer composite fiber core prepared in Comparative Examples 1 and 2 are all lower than those in Examples 1-3. It can be seen that by first grinding and sieving the corn stalks and preparing them into a corn stalk suspension, and then adding sodium hydroxide solution and sodium chloroacetate to react respectively to prepare carboxymethyl corn stalk cellulose, and then mixing the carboxymethyl corn stalk cellulose with acrylic acid, acrylamide and mesoporous silica nanospheres, and adding N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid to react under the initiation of potassium persulfate, on the one hand, due to the carboxymethyl corn stalk fiber, N,N′-methylenebisacrylamide The combined effect of acrylic acid and acrylamide-2-methylpropane sulfonic acid can make the composite super absorbent resin made of acrylic acid and acrylamide form a denser and more numerous three-dimensional network structure, while the addition of mesoporous silica nanopowder can improve the network structure stability of the composite super absorbent resin, thereby significantly improving the water absorption rate of the prepared composite absorbent resin. On the other hand, due to the high salt resistance of acrylamide, the steric hindrance of carboxymethyl corn straw cellulose and the negatively charged groups of 2-acrylamide-2-methylpropane sulfonic acid can form multiple protection mechanisms to prevent salt ion interference, thereby effectively improving the salt resistance of the composite absorbent resin, and then improving its water absorption rate for artificial blood / urine.

[0151] Test 2:

[0152] The antibacterial performance of the multi-layer composite fiber cores prepared in Examples 1-3 and Comparative Examples 3-6 against Staphylococcus aureus and Escherichia coli was tested with reference to the oscillation method of GB / T20944.3-2008. The results are shown in Table 2.

[0153] Table 2: Antibacterial performance test comparison table of Examples 1-3 and Comparative Examples 3-6

[0154] Staphylococcus aureus inhibition rate (%) Escherichia coli inhibition rate (%) Example 1 98.4 99.7 Example 2 98.5 99.6 Example 3 98.2 99.8 Comparative Example 3 86.4 89.3 Comparative Example 4 94.3 95.2 Comparative Example 5 96.5 97.6 Comparative Example 6 97.8 98.2

[0155] Test 3:

[0156] The reduction rates of ammonia and acetic acid gas of the multi-layer composite fiber cores prepared in Examples 1-3 and Comparative Example 3 were tested with reference to GB / T 33610.2-2017 "Determination of deodorizing properties of textiles Part 2: Detection tube method"; the reduction rates of isovaleric acid gas of the multi-layer composite fiber cores prepared in Examples 1-3 and Comparative Example 3 were tested with reference to ISO 17299-3-2014 "Determination of deodorizing properties of textiles Part 3: Gas chromatography", and the results are shown in Table 3.

[0157] Table 3: Deodorization performance test comparison table of Examples 1-3 and Comparative Example 3

[0158] Ammonia reduction rate (%) Acetic acid gas reduction rate (%) Isovalerate gas reduction rate (%) Example 1 78.3 93.2 80.2 Example 2 78.5 93.3 79.7 Example 3 78.8 93.5 80.3 Comparative Example 3 4.8 10.3 5.2

[0159] It can be seen from Tables 2 and 3 that the antibacterial rates of Staphylococcus aureus and Escherichia coli of the multi-layer composite fiber core prepared in Comparative Example 3 are lower than those in Examples 1-3, and the reduction rates of ammonia, acetic acid gas and isovaleric acid gas are also lower than those in Examples 1-3. It can be seen that by first mixing monomers of glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile), then adding the mixed monomers and sodium p-styrene sulfonate to a mixed solution of anhydrous ethanol and deionized water for reaction to prepare an intermediate, then dissolving the intermediate in deionized water, adding chitosan solution and hexadecyltrimethylammonium bromide for reaction to prepare an antibacterial additive, and the antibacterial additive is prepared together with activated clay micropowder. After being added into the viscose spinning solution and spun into antibacterial and deodorizing viscose fibers, on the one hand, the epoxy groups in the intermediate molecular chain are combined with the amino groups in the chitosan structure, so that the water solubility of the obtained antibacterial additive is enhanced, which is conducive to better interaction with bacteria. On the other hand, the sodium sulfonate groups in the intermediate molecular chain are ion-exchanged with hexadecyltrimethylammonium bromide, so that the positive charge density on the surface of the obtained antibacterial additive is increased to improve its antibacterial activity. The activated white clay micropowder contains a large number of micropores and has good adsorption properties, and can effectively absorb odorous gases. Therefore, after the antibacterial and deodorizing viscose fibers are made into a multi-layer composite fiber core, the antibacterial and deodorizing properties of the multi-layer composite fiber core can be improved.

[0160] In addition, the antibacterial rates of Staphylococcus aureus and Escherichia coli of the multi-layer composite fiber core prepared in Comparative Example 4 are lower than those in Comparative Example 5 and Comparative Example 6, while those in Comparative Example 5 and Comparative Example 6 are lower than those in Examples 1-3. It can be seen that by first using thyme essential oil and β-cyclodextrin as raw materials to prepare thyme essential oil microcapsules, and then mixing the thyme essential oil microcapsules with neem tree fruit extract to prepare an antibacterial treatment liquid, and using the antibacterial treatment liquid to treat a fiber web made of antibacterial and deodorizing viscose fiber and hydrophilic polyolefin two-component fiber, the thyme essential oil microcapsules can synergistically improve the antibacterial properties of the fiber web with the neem tree fruit extract, thereby further improving the antibacterial properties of the multi-layer composite fiber core made of the fiber web.

[0161] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a multi-layer composite fiber core, characterized in that: The steps include: S1: Preparation of mesoporous silica nanospheres The anhydrous ethanol and concentrated ammonia water are uniformly mixed, and then hexadecyl trimethyl ammonium bromide is added, and after stirring and dispersing, sodium dodecyl sulfate and ethyl orthosilicate are added to react to prepare a precursor, and then the precursor is placed in isopropanol, after ultrasonic treatment, centrifuged, washed and dried to obtain mesoporous silica nanospheres; S2: Preparation of composite superabsorbent resin The corn stalks are ground and dispersed in deionized water, and then sodium hydroxide solution and sodium chloroacetate are added to react to prepare carboxymethyl corn stalk cellulose, and then acrylic acid, acrylamide, carboxymethyl corn stalk cellulose and the above-mentioned mesoporous silica nanospheres are fully mixed, and N,N′-methylenebisacrylamide, 2-acrylamide-2-methylpropanesulfonic acid and potassium persulfate are added to react to obtain a composite super absorbent resin; S3: Preparation of antibacterial additives Glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile) are fully stirred and mixed, and then added together with sodium p-styrene sulfonate into a mixed solution of anhydrous ethanol and deionized water, and the mixture is heated to react to prepare an intermediate, and then the intermediate and chitosan are dissolved to prepare an intermediate solution and a chitosan solution respectively, and finally the intermediate solution is added into the chitosan solution to react, and then hexadecyltrimethylammonium bromide is added to continue the reaction to obtain an antibacterial additive; S4: Preparation of antibacterial and deodorizing viscose fibers The antibacterial additive is dissolved in deionized water, and then activated clay powder is added, and after ultrasonic dispersion for 1-2 hours, it is added to the viscose spinning solution, stirred and mixed evenly, and allowed to stand for 2-3 hours. After filtering, degassing and aging, wet spinning is performed to obtain antibacterial and deodorizing viscose fibers; S5: Preparation of antimicrobial treatment solution β-cyclodextrin and thyme essential oil are respectively prepared into β-cyclodextrin dispersion and thyme essential oil solution, then the thyme essential oil solution is added into the β-cyclodextrin dispersion to prepare thyme essential oil microcapsules, which are then added into the aqueous solution of neem tree fruit extract, and after ultrasonic treatment, an antibacterial treatment solution is obtained; S6: Preparation of antimicrobial treated web The antibacterial and deodorizing viscose fiber and the hydrophilic polyolefin bicomponent fiber of equal weight are mixed and opened, and fed into a carding machine to form a fiber web, and then the fiber web is immersed in the antibacterial treatment liquid according to a solid-liquid ratio of 1g: (22-28)mL, and a cross-linking agent is added, and the fiber web is treated at 80-90°C for 1-2h, and then taken out and dried to obtain an antibacterial treated upper fiber web and an antibacterial treated lower fiber web; S7: Preparation of multi-layer composite fiber core The composite super absorbent resin is evenly added to the antibacterial treated upper fiber web and the antibacterial treated lower fiber web through an online powder spreading device, and then the antibacterial treated upper fiber web and the antibacterial treated lower fiber web loaded with the composite super absorbent resin are compounded and fed into a hot air blower for reinforcement to obtain a multi-layer composite fiber core.

2. The method for preparing a multi-layer composite fiber core according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1: Thoroughly mix anhydrous ethanol and concentrated ammonia water at a volume ratio of (6-8):1, then add hexadecyltrimethylammonium bromide at a solid-liquid ratio of 1g:(145-155)mL, stir and disperse to obtain a mixed dispersion; S1.2: Add sodium dodecyl sulfate and tetraethyl orthosilicate to the above mixed dispersion, and stir the mixture at a rate of 1000-1200 r / min for 3-4 hours, centrifuge, wash and dry to obtain a precursor; S1.3: The above precursor is placed in isopropanol, stirred for 8-10 hours, and then ultrasonically treated for 30-40 minutes. After centrifugal separation, the precipitate is washed with isopropanol for 3-5 times, and then dried to obtain mesoporous silica nanospheres.

3. The method for preparing a multi-layer composite fiber core according to claim 2, characterized in that: S2 specifically includes the following steps: S2.1: Place corn stalks in a grinder, grind them thoroughly, pass through a 80-120 mesh sieve, and mix them thoroughly with deionized water at a solid-liquid ratio of 1 g: (90-100) mL to obtain a corn stalk suspension; S2.2: Add a 20% sodium hydroxide solution by volume to the corn straw suspension, and heat and stir at 35-45°C for 1-2h, then raise the temperature to 70-80°C, add sodium chloroacetate at a solid-liquid ratio of 1g:(8-10)mL, and continue to react for 1-2h to obtain a carboxymethyl corn straw cellulose solution; S2.3: filtering the carboxymethyl corn straw cellulose solution, washing with distilled water until neutral, and drying to obtain carboxymethyl corn straw cellulose; S2.4: Add acrylic acid, acrylamide and carboxymethyl corn straw cellulose into deionized water, stir and mix thoroughly, then add the mesoporous silica nanoparticles prepared in step S1.3, and disperse them by ultrasonic for 10-20 minutes to obtain a mixed solution, wherein the mass ratio of acrylic acid, acrylamide, carboxymethyl corn straw cellulose and deionized water is (6-8): (1-2): 1: (25-35), and the solid-liquid ratio of mesoporous silica nanopowder to deionized water is 1g: (40-50)mL; S2.5: Add N,N′-methylenebisacrylamide and 2-acrylamide-2-methylpropanesulfonic acid to the above mixed solution at a solid-liquid ratio of 1g:(3-5)g:(60-70)mL. After thorough mixing, add 10% by mass potassium persulfate solution, and heat under reflux at 60-70°C for 3-4h. After drying, crushing and sieving, a composite super absorbent resin is obtained, wherein the volume ratio of potassium persulfate solution to the mixed solution is 1:(35-45).

4. The method for preparing a multi-layer composite fiber core according to claim 1, characterized in that: S3 specifically includes the following steps: S3.1: Glycidyl methacrylate, butyl acrylate and 2,2″-azo(2-methylpropionitrile) are thoroughly stirred and mixed in a mass ratio of (8-10):(12-13):1 to obtain a mixed monomer; S3.2: Mix anhydrous ethanol and deionized water in a volume ratio of (5-6):1, heat to 70-80°C, add the above-mentioned mixed monomer and sodium p-styrene sulfonate, keep the temperature for 3-4h, dialyze and vacuum freeze-dry to obtain an intermediate; S3.3: dissolving the intermediate in deionized water, and dissolving chitosan in acetic acid solution to obtain an intermediate solution and a chitosan solution; S3.4: Add the intermediate solution to the chitosan solution, heat at 60-70°C for reaction for 6-8h, then add hexadecyltrimethylammonium bromide, continue the reaction for 3-4h, dialyze and vacuum freeze-dry to obtain an antibacterial additive.

5. The method for preparing a multi-layer composite fiber core according to claim 1, characterized in that: S5 specifically includes the following steps: S5.1: mixing β-cyclodextrin and thyme essential oil with deionized water and anhydrous ethanol, respectively, to obtain a β-cyclodextrin dispersion with a mass fraction of 60-70% and a thyme essential oil solution with a concentration of 75-85%; S5.2: adding the thyme essential oil solution to an equal volume of the β-cyclodextrin dispersion, heating and shaking at 60-70°C for 2-3 hours, and then standing at 3-5°C for 8-10 hours to perform a curing reaction to obtain thyme essential oil microcapsules; S5.3: Dissolve the neem fruit extract in distilled water at a solid-liquid ratio of 1 g:(10-12) mL, add the above-mentioned thyme essential oil microcapsules while stirring, and then ultrasonically treat for 20-30 minutes to obtain an antibacterial treatment solution, wherein the mass ratio of thyme essential oil microcapsules to neem fruit extract is 1:(3-4).

6. The method for preparing a multi-layer composite fiber core according to claim 2, characterized in that: The mass ratio of sodium dodecyl sulfate to hexadecyltrimethylammonium bromide is 1:(11-13), and the volume ratio of ethyl orthosilicate to the mixed dispersion is 1:(110-120).

7. The method for preparing a multi-layer composite fiber core according to claim 4, characterized in that: The solid-liquid ratio of sodium p-styrene sulfonate to the total amount of anhydrous ethanol and deionized water is 1 g:(7-9) mL, and the mass ratio of sodium p-styrene sulfonate to the mixed monomer is (1.1-1.2):

1.

8. The method for preparing a multi-layer composite fiber core according to claim 4, characterized in that: The solid-liquid ratio of the antibacterial additive to deionized water is 1 g: (20-30) mL, and the mass ratio of activated clay powder to the antibacterial additive is 1: (13-15), and the addition amount of activated clay powder is (0.01-0.03) g / mL viscose spinning solution.

9. The method for preparing a multi-layer composite fiber core according to claim 1, characterized in that: The antibacterial treated upper fiber web uses antibacterial and deodorizing viscose fiber with a linear density of 1.67 dtex and hydrophilic polyolefin bicomponent fiber with a linear density of 6.67 dtex, and the antibacterial treated lower fiber web uses antibacterial and deodorizing viscose fiber with a linear density of 1.67 dtex and hydrophilic polyolefin bicomponent fiber with a linear density of 2.22 dtex.

10. A multi-layer composite fiber core, characterized in that: It is prepared by the method for preparing a multi-layer composite fiber core according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing super water absorption resin from waste corn straw

    CN110818839A

  • Nonwoven absorbent core material and preparation process thereof

    CN110840658A